KESIAPAN GURU MADRASAH DI KOTA SEMARANG DALAM MENGHADAPI PELAKSANAAN PPG - Farikh, Amin (Kopertais Wilayah X Jawa Tengah, 2015)
AbstractProfessional Teacher Education (PTE/ PPG) can be regarded as a program to improveÂ the competence of todayâs most important teacher. This program is not solely theÂ learning process of the teachers, but also as a starting point increase teachersâ welfareÂ through the provision of teaching certi